Asas etika alam sekitar dalam konsep pembangunan mampan - Mashitoh Yaacob (Environmental Management Society, Malaysia, 2001)
The concept of sustainable development is the best concept available thus far for balancing development and environment. The view is shared at the international level. As such the concept of sustainable development is incorporated by many countries including Malaysia, in developing their environmental resources. In the justification of ethical processes in its implementation a number of basic questions has to be observed and scrutinized. What is the ethical base embedded in the concept of sustainable development? Besides, how far is the concept capable of providing environmental ethics in carrying out sustainable development? This article generally tries to answer both questions in particular by studying the ability of the concept in preparing a base on environmental ethics in its implementation through the action plan, the Agenda 21. Agenda 21 is chosen because it contains the ingredients for the implementation of sustainable development concept